ANALISIS PENGARUH PUBLIC RELATIONS DAN PENCITRAAN TERHADAP MINAT KULIAH DI PERGURUAN TINGGI SWASTA - Ari Susanti (JURNAL LENTERA BISNIS, 2012)
The purpose of this study is to find the correlation between Public Relation and the impression as independent variables to the attentiveness in studying in private universities. The data for the study is taken from questionnaire given to 206 samples from total 406 students. The data from the questionnaire is analyzed by using the software SPSS version 17.0 in order to get the validity and reliability scores, normality, correlation and multi regression, anova, and T-test to analyze the hypothesis. The study approves that there is significant correlation between public relations to the students interest to study in university, correlation between the impression of the university to the students interest to study in university, and lastly the correlation between public relations and the impression mutually to the students interest to study in university. The determination coefficient score (R2) is 0.504 or 50.4%. This means that 50.4% of the students interest to study in university is able to be explained the variable of public relation and the impression as the independent variables. Meanwhile, the other variables are explained by other variables outside of the model of research. The function which is taken from the study is Y = 42.411 + 0.183 X1 + 0.464 X2 +  Key Words : Public Relations, Impression, Students Interest to study